New and Advanced Methods in Detection of Fruit Juice Adulteration: Focusing on Nano-Biosensor - Samira Shokri; Mahya Soltani; Yeganeh Mazaheri; Alieh Rezagholizade-shirvan; Mansoureh Mohammadi; Nabi Shariatifar; Tayebeh Zeinali (Journal of Spectroscopy)
One of the most popular products made from fruit is juice, which is consumed as a snack by people of all ages due to its high content of polyphenols and vitamins. Therefore, the prevalence of adulteration in juices is very high, and ensuring the authenticity and quality of juices is a major concern for those responsible for monitoring food safety for the public. The most common frauds in fruit juices include adding water, sugar, organic acids, and other juices clouding agents and exceeding the permitted amount of sulfites. Having knowledge of the types of fraud in fruit juices and their detection methods is essential for developing more efficient detection methods. Chromatographic techniques, such as high-performance liquid chromatography (HPLC) and gas chromatography (GC), are commonly used to determine the purity of fruit juices. Among the new methods for detecting counterfeit fruit juice, the development of bio-nanosensors is particularly notable. These sensors reduce sample volume, analytical time, costs, and solvent consumption and will be discussed further in this study. Therefore, this review will explain the basic analytical approaches and chemometric tools used to assess the authenticity of fruit juice and identify any adulteration in the juice.